Comparative Assessment of the Clinical Efficacy of Antihypoxants in Patients with Acute Poisoning by Psychotropic Agents - A. V. Alekhnovich; K. K. Ilyashenko; A. N. Yelkov; N. F. Lezhenina; A. S. Livanov (Общая реаниматология, 2009)
To compare the clinical efficacy of antihypoxants having different mechanisms of action, the authors studied the results of treatment in 218 patients with severe acute poisoning by psychotropic drugs. The patients were divided into 1 control and 3 study groups in which antihypoxic agents, such as mexicor, cytoflavin, and cortexin, complemented a complex of therapeutic measures. Their use was ascertained to reduce the duration of coma, acute respiratory failure, the incidence of pneumonias, and the length of stay in an intensive care unit and a hospital and to substantially decrease mortality. The authors recognize it advisable to include antihypoxants into a complex of therapeutic measures for poisoning by psychotropic drugs. Key words: antihypoxants, acute intoxications, psychotropic agents.